If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -6 = -22 Reorder the terms: -6 + 4y = -22 Solving -6 + 4y = -22 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4y = -22 + 6 Combine like terms: -6 + 6 = 0 0 + 4y = -22 + 6 4y = -22 + 6 Combine like terms: -22 + 6 = -16 4y = -16 Divide each side by '4'. y = -4 Simplifying y = -4
| 2(x-4)+3=4x+7 | | 6x^2+47x+92=0 | | (2x+28)=(3x+137) | | -24-7n=-8(3-6n) | | 42=3(2-3n)-6 | | -19=3(7+3n)+8(8n-5) | | 180=111-u | | -12+19/-7= | | -12+-42/-7= | | 60x^2-20x+1=0 | | 84=2w+2L-3 | | 15y-11y=20 | | -12+-126/-7= | | x^2+(x*y)=120 | | 84+3x=1x | | -9u-5+6=19 | | -12+h/7=6 | | -a+5+6a=1+5a+3 | | -12+h/7= | | 8x+4(2-3x)=36-6x | | (4x-3)+3(3x+6)=5x-1 | | 4x^3-33x^2-30x=0 | | 2x+17+3x-4=180 | | 32=2x+14 | | 0.625=-0.50x | | 88+1.5h=94+2h | | 85=3(x-1)+8x | | -5(k-1)-(-6k+1)=9 | | 7a^2+49a+60=0 | | (sin(x))*2=116 | | 1x+-7=2x+-6 | | (sin(x))2=116 |